Translation, cross-cultural adaptation, reliability, and validation of the italian version of the Foot and Ankle Disability Index (FADI) - Leigheb, Massimiliano; Rava, Emanuele; Vaiuso, Dario; Samaila, Elena Manuela; Pogliacomi, Francesco; Bosetti, Michela; Grassi, Federico Alberto; Sabbatini, Maurizio (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim of the work: Foot-and-Ankle-Disability-Index (FADI) is one of the most widely used evaluation questionnaires for this anatomical district, but an italian validated version lacks and is necessary to properly evaluate italian people. In fact a correct interpretation of the items by patients is essential to obtain a precise subjective response, making the questionnaire valid to evaluate patients’ satisfaction and wellness. Our purpose was to translate and culturally adapt into Italian the FADI questionnaire, and to check its reproducibility and validity. Materials and Methods: The original english version of FADI questionnaire was translated into Italian and checked for medical part coherence. It was submitted to 10 italian randomized patients to verify a correct cultural adaptation, and then to other 50 randomized patients operated at their ankle or hallux to assess intra- and inter-observer reproducibility by the Pearson’s-Correlation-Coefficient (PCC) and the Intra-Class-Correlation (ICC) coefficient. Moreover, Short-Form-36 (SF36) questionnaire for Quality-of-Life and Visual-Analogue-Scale (VAS) for pain were also administered to the same 60 people and compared to italian-FADI to perform validation analysis by PCC and ICC coefficient. Results: Cultural adaptation of the translated version of the scale resulted good in terms of understandability by patients. An optimal correlation of the inter- and intra-observer reproducibility was obtained. The correlation obtained between FADI and SF-36 as well as between FADI and VAS indicates success in the validation process. Conclusions: Validation of the FADI italian version has been performed successfully, its use can be considered appropriate and is indicated in italian clinical practice. (www.actabiomedica.it)